Exclusive Breastfeeding Practice and Its Association with Breastfeeding Self-Efficacy among Mothers Giving Birth during the COVID-19 Pandemic in Indonesia: A Brief Report - Angelina, Angelina; Lesmanadjaja, Alicya; Agung, Fransisca Handy; Octavius, Gilbert Sterling (Journal of Maternal and Child Health, 2021)
Background: Breast milk is the best nutrition for most infants, and current recommendations encourage mothers to keep giving breast milk during the COVID-19 pandemic. This study aimed to examine Exclusive Breastfeeding Practice and its association with  breastfeeding self-efficacy in lactating women during COVID-19 pandemic. Subjects and Method: This is an analytic cross-sectional study involving mothers giving birth since March 2020 and their infants aged under 6 months. An online-based questionnaire, including the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF), was distributed through social media from April to September 2020. The dependent variable was exclusive breastfeeding rate, and the independent variables were BSES-SF score, mother working status, educational level, place of birth, birth method, and COVID-19 status. Results: There were 113 respondents, and the rate of exclusive breastfeeding was 79.6%. Self-efficacy score in mothers who give exslusive breastfeeding (Mean= 58.4; SD= 0.8) was higher than non exclusive breastfeeding (Mean= 44.8; SD= 13.4) and it was statisfically significant (p <0.001). Conclusion: This study showed that during the COVID-19 pandemic exclusive breastfeeding rate might remain high in populartions with good breastfeeding self-efficacy.